Pengaruh Geometri Jalan Terhadap Produktivitas Alat Angkut - Rizky Noor Fitriadi; Iswandaru; Elfida Moralista (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. Based on the actual conditions in the field, there are several road geometries that are not in accordance with the standards resulting in high traffic density. This causes the actual productivity of the HD 785 conveyance at the KGU South front of 108.2 BCM / Hour / Tool to not reach the conveyance productivity target of 115.23 BCM / Hour / Tool. Therefore, it is necessary to conduct this research to increase the productivity of hauling equipment by improving road geometry. The research was conducted on road geometry focusing on the standardization of Jalan Pandawa. Analysis using the comparative method was carried out with reference to KEPMEN ESDM No. 1827 of 2018 and the American Association of State Highways and Transportation Officials (AASHTO) on road geometry, Rolling Resistance and traffic density, so as to achieve the planned hauling equipment productivity target. Based on the research results, recommendations are obtained to achieve the HD 785 conveyance productivity target, namely by standardizing road geometry with a road grade of no more than 8%, Rolling Resistance of 2.11% with a subsidence state of 2.5 cm, and traffic density of no more than 80% of the maximum density of Jalan Pandawa with a total of 27 units in loaded conditions and 22 units in empty conditions. The productivity of the conveyance increased by 19.55% from 108.2 BCM/Hour/Tool to 129.36 BCM/Hour/Tool so that the productivity target of the conveyance was achieved. Abstrak. Berdasarkan pada kondisi aktual di lapangan terdapat beberapa geometri jalan yang tidak sesuai dengan standar sehingga terjadi traffic density yang tinggi. Hal tersebut menyebabkan produktivitas aktual alat angkut HD 785 di front KGU Selatan sebesar 108,2 BCM/Jam/Alat tidak mencapai target produktivitas alat angkut yaitu sebesar 115,23 BCM/Jam/Alat. Oleh sebab itu maka perlu dilakukan penelitian ini untuk meningkatkan produktivitas alat angkut dengan perbaikan geometri jalan. Penelitian dilakukan terhadap geometri jalan yang berfokus pada standarisasi Jalan Pandawa. Analisis menggunakan metode komparatif dilakukan dengan mengacu pada KEPMEN ESDM No. 1827 tahun 2018 dan American Association of State Highways and Transportation Officials (AASHTO) terhadap geometri jalan, Rolling Resistance serta traffic density, sehingga tercapai target produktivitas alat angkut yang sudah direncanakan. Berdasarkan hasil penelitian didapatkan rekomendasi untuk mencapai target produktivitas alat angkut HD 785 yaitu dengan melakukan standarisasi geometri jalan dengan grade jalan tidak lebih dari 8%, Rolling Resistance sebesar 2,11% dengan keadaan subsidensi 2,5 cm, serta traffic density tidak lebih dari 80% dari maksimum density Jalan Pandawa dengan total 27 unit pada kondisi muatan serta 22 unit pada kondisi kosongan. Produktivitas alat angkut meningkat 19,55% dari 108,2 BCM/Jam/Alat sampai ke 129,36 BCM/Jam/Alat sehingga target produktivitas alat angkut tercapai.